2015
DOI: 10.1128/jvi.01370-15
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-Associated Virus Type 2 Rep68 Can Bind to Consensus Rep-Binding Sites on the Herpes Simplex Virus 1 Genome

Abstract: e Adeno-associated virus type 2 is known to inhibit replication of herpes simplex virus 1 (HSV-1). This activity has been linked to the helicase-and DNA-binding domains of the Rep68/Rep78 proteins. Here, we show that Rep68 can bind to consensus Repbinding sites on the HSV-1 genome and that the Rep helicase activity can inhibit replication of any DNA if binding is facilitated. Therefore, we hypothesize that inhibition of HSV-1 replication involves direct binding of Rep68/Rep78 to the HSV-1 genome.A deno-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Compared to the positive control (wt Rep) both Rep mutants (K340H and D371Y) significantly rescued pHSVGFP titers by more than 10-fold and at comparable levels ( Fig 2C ). The helicase-null mutant Rep-K340H, which cannot support AAV2 replication, was previously known to allow HSV-1 replication [ 38 , 44 ]. As the mutant Rep-D371Y allowed HSV-1 replication, we expected that it may not support AAV2 DNA replication either.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Compared to the positive control (wt Rep) both Rep mutants (K340H and D371Y) significantly rescued pHSVGFP titers by more than 10-fold and at comparable levels ( Fig 2C ). The helicase-null mutant Rep-K340H, which cannot support AAV2 replication, was previously known to allow HSV-1 replication [ 38 , 44 ]. As the mutant Rep-D371Y allowed HSV-1 replication, we expected that it may not support AAV2 DNA replication either.…”
Section: Resultsmentioning
confidence: 99%
“…We and others have demonstrated that the AAV2 Rep domains responsible for the inhibition of HSV-1 DNA replication include the combined DNA-binding and the ATPase/helicase domains [ 38 , 41 ]. Direct binding of the AAV2 Rep proteins to the HSV-1 DNA and the subsequent activity of the ATPase/helicase domain have been shown to account at least in part for the Rep-mediated inhibition of HSV-1 replication [ 44 ]. This interaction may cause DNA lesions which are not compatible with effective HSV-1 DNA replication.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations